Hubungan Karakter Religious Terhadap Hasil Belajar Peserta Didik pada Muatan Pelajaran Agama Islam - Juwita Saputri; Roy Andre Ferdinan (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of this Study: The purpose of this study was to compare the religious character and the peace-loving character in religious learning Research Methods: This type of research uses quantitative research. This study uses various variables as research categories, namely religious and peace-loving characters, with a sample of 15 students. Data analysis used descriptive and inferential statistics. Main Findings: The result is that each variable from religious character to learning outcomes with a value of sig < 0.05 and in each dominant variable in the excellent category Novelty of Research: The novelty of this research is to examine the relationship of religious characters in learning Islamic religious content in elementary schools. This research aims to describe the relationship of religious characters carried out by distributing questionnaires to students on learning Islamic religion in elementary schools.